ETNOCULTURE AS A RESEARCH OBJECT OF PHILOSOPHICAL AND ETHNOLOGICAL SCIENCES - Alimasov Viktor Aleksandrovich (Web of Journals Publishing, 2024)
In this article investergatied philosophical and etnological interpryes "etnoculture" and his please in the sostial-historical prossersies, shape of life, traditions and integration prossersies by people mass.